The Effect of Brain-Based Learning Model on Student Physics Learning Outcomes - Yusri Handayani; Nurfadilah Nurfadilah (Kasuari: Physics Education Journal (KPEJ), 2021)
This study has the aim of analyzing student learning outcomes after being taught by using a brain based learning model and analyzing the influence/impact of brain based learning on student learning outcomes. This research is a true experimental posttest only control design, which consists of a control class of 34 students and an experimental class of 34 students. The independent variable of this research is the brain based learning model, while the dependent variable is the physics learning outcome. The research instrument used the form of multiple choice tests on static fluid material as many as 25 questions. The data analysis technique used consisted of descriptive analysis and inferential analysis, namely the t test using the SPSS 24 application, but previously the initial assumption test was carried out as a normality test and homogeneity as a t test requirement. If the initial assumption test results do not meet, then non-parametric analysis will be used. The results of descriptive analysis can be stated that the average score of students' physics learning outcomes with brain based learning as a learning model is higher than in conventional classes or classes that do not use brain based learning. The high results of student learning in classes with brain based learning are due to the influence/impact of learning by using this model. This research can give results that there is an influence/impact of brain based learning as a learning model on physics learning outcomes. Students optimize their brain work if they use a brain based learning model so that physics learning outcomes increase.